BIST Architecture for Magnetic Memories - Babayan, Armen V. (Mathematical Problems of Computer Science, 2021)
Magnetic random-access memory (MRAM) is one of the emerging memory technologies, which can be considered as the next universal memory because of its good parameters. Nevertheless, this type of memory is not guaranteed from defects and it is very important to understand the fault typology and develop a test solution that addresses these faults. In this paper a Built-in Self-Test (BIST) solution is presented,which is specifically tailored for MRAMs and efficiently deals with MRAM specific faults.